1,3,4-Oxadiazoles as Telomerase Inhibitor: Potential Anticancer Agents - Bajaj, Shalini; Roy, Partha P.; Singh, Jagadish (Anti-Cancer Agents in Medicinal Chemistry, 2017)
Cancer is a rapidly growing disease of current era which poses a major life threaten situation to human beings. Continuous research is going on in the direction to develop effective molecules for the treatment of the cancer. These efforts include searching of more active heterocyclic compounds possessing potential anticancer activity. The 1,3,4-Oxadiazole scaffold is a five member heterocyclic ring having versatile activities and created interest for synthetic organic and medicinal chemists for the designing of novel compounds having anticancer activity. The important mechanism behind tumor suppression by 1,3,4-Oxadiazole is related with the inhibition of different growth factors, enzymes and kinases etc. The current literature surveys revealed that 1,3,4-Oxadiazole is a promising lead for anti-cancer agents by the inhibition of telomerase activity. In cancerous cells telomerase enzyme is activated which maintains and restores the telomere which leads to cell proliferation. The telomerase inhibitors with enhanced specificity and improved pharmacokinetics have been considered for design and development of novel anti-cancer agents. This review focuses primarily on telomerase enzyme its function and mechanism of action. It also describes the interaction of telomerase enzyme with 1,3,4-Oxadiazole inhibitors including their structure activity relationships (SARs). With the knowledge of this molecular target, structural insights and SARs, this review may be helpful for (medicinal) chemists to design more potent, safe, selective and cost effective anti-cancer agents.
Keywords: docking